HUBUNGAN ANTARA TIPE TRAUMA DENGAN GEJALA PTSD PADA SISWA SDN PASCAERUPSI MERAPI DI KECAMATAN CANGKRINGAN SLEMAN PROVINSI DAERAH ISTIMEWA YOGYAKARTA - , Emi Kosvianti; , Prof. dr. M. Hakimi, SpOG(K), Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Background: Post traumatic stress disorder (PTSD) is an anxiety disorder, which is following psychological stress and traumatic events such as natural disasters, accidents, wars or rapes. The trauma of Mount Merapi eruption is divided into three types namely loss of property, loss of life and multiple losses. Children are often considered as a group which is very vulnerable toward disaster, because they are physically, psychologically and behaviors still on the development stage. Responses of children toward disaster are varies, ranging from mild stress to severe and prolonged stress that can develop into PTSD. Research Objectives: To identify the differences of PTSD symptoms based on the type of trauma of elementary school students post-eruption of Mount Merapi in Cangkringan District, Sleman DIY. Method: This research was an observational with cross-sectional design by applying quantitative and qualitative approaches (conducting in-depth interview). The independent variable is type of trauma and the dependent variable is PTSD symptoms. The measurement of trauma and PTSD were conducted by using modified UCLA-PTSD Index (child version-revision 1). Based on cluster and total population sampling, the sample were 100 students. The bivariate analysis will be examined through anova, chi square, independent t-test and product moment correlation test, while the multivariate analysis used path analysis. Results: There was no significant in PTSD symptoms of students who have multitrauma, loss of life, and loss of property. Only avoidance and support seeking coping strategies, which have significant relationship to PTSD symptoms. And there was no relationship between gender and social support with PTSD symptoms. The result of path analysis showed that statistically only coping strategies which have a meaningful relationship with PTSD symptoms. Conclusion: There is no significant difference in PTSD symptoms of students who have experienced multitrauma, loss of life and loss of property. Only coping strategies which have a meaningful relationship with PTSD symptoms.